Ortho–para conversion in the solid hydrogens at high pressures: High-Pressure Studies - Strzhemechny, M.A.; Hemley, R.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
At low pressures the ortho–para conversion in H2 and D2 is a slow process governed by the magnetic dipole interaction of nuclear magnetic moments, phonons being the main energy sink. As the pressure is raised to a few GPa and the Debye temperature increases substantially, the conversion energy finds itself in an area where phonon states are depleted and conversion slows down. The recent Raman and NMR experiments showed that the conversion rate in H2 after an initial slowdown predicted by theory increases immensely. As for solid D2, conversion rates have apparently not yet been directly measured under pressure. In order to explain the anomaly observed in H2, we have suggested a new conversion mechanism, in which the basic conversion-producing interaction only initiates conversion whereas the energy is removed by rotational excitations via the stronger electric quadrupole-quadrupole interaction. Estimated conversion rates are in good qualitative agreement with available experimental observations. Here we extend the theory to solid D2 taking into account the differences between H2 and D2 in the molecular and solid-state parameters. The new libron-mediated channel is predicted to result for D2 in conversion rates under pressure that are by an order of magnitude larger than at P = 0.